Exit - Bauer, Belinda, 1962- (Atlantic Monthly Press, 2020)
"Felix Pink is a retired widower leading a boring life and hoping to die a boring death. He volunteers as an Exiteer-someone who sits with terminally ill people as they die by suicide, assisting with logistics and lending moral support, then removing the evidence to take the burden off their loved ones. When Felix lets himself in to Number 3 Black Lane, he's there to perform an act of kindness and charity: to keep a dying man company as he takes his final breath. But just fifteen minutes later Felix is on the run from the police after making the biggest mistake of his life. Now his world is turned upside down as he tries to discover whether what went wrong was a simple mistake-or murder"--